2014
DOI: 10.3109/09638288.2014.885091
|View full text |Cite
|
Sign up to set email alerts
|

Determinants influencing the implementation of home-based stroke rehabilitation: a systematic review

Abstract: A more complete and detailed overview of existing determinants of HBSR is needed to assist professionals and organizations in decision-making on HBSR implementation and development of suitable strategies for implementation. Implications for Rehabilitation Committed professionals and a smooth transfer to the home-environment are essential elements for home-based rehabilitation or early supported discharge. The determinants related to the client include age, needs, stability and severity of the stroke as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 20 publications
(83 reference statements)
0
40
1
Order By: Relevance
“…These results somewhat contrast with the promising results from studies on early supported discharge (ESD) and home rehabilitation programs, which show similar or better outcomes of patient treatment when the length of specialist health care stay is reduced (23,(42)(43)(44)(45)(46). However, particular ESD studies presuppose extra SpHC effort in patient transition, performed in the PrHC setting, offering close collaboration and support in the homecoming phase (21,22).…”
Section: Discussioncontrasting
confidence: 53%
“…These results somewhat contrast with the promising results from studies on early supported discharge (ESD) and home rehabilitation programs, which show similar or better outcomes of patient treatment when the length of specialist health care stay is reduced (23,(42)(43)(44)(45)(46). However, particular ESD studies presuppose extra SpHC effort in patient transition, performed in the PrHC setting, offering close collaboration and support in the homecoming phase (21,22).…”
Section: Discussioncontrasting
confidence: 53%
“…A recent review 21 indicated that inconsistency in values and beliefs from professionals leads to lower implementation. Apart from a multidisciplinary expert team, success is also based on developing a collaborative approach to rehabilitation between the healthcare team and the patient and developing problem-solving skills in all, patient and provider.…”
Section: Strokementioning
confidence: 99%
“…This evaluation should also consider the processes and outcomes from the experiences of people receiving the program. 21 The work by Nordin et al 20 in summarizing the expectations of patients with respect to ESD provides information on how to move forward with implementing ESD. A key expectation was that the team would provide support, so patients could manage and feel comfortable and safe being at home.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Both individuals and professionals can be addressed in a single study design. Simeonsma's study, which was referred to as an example in cell 5 of a study of client satisfaction with services, also involved interviews with professionals about providing the addressed services and the cooperation between service levels [31]. Another example is Helgøy et al who look into how persons with mobility-disability understand independence and how the wide variety of service providers they rely on have contrasting understandings of independent ways of living [41].…”
Section: Complexitymentioning
confidence: 99%